Properties of cloud computing for small and medium sized enterprises - Hauke, Krzysztof; Owoc, Mieczysław L. (Własności cloud computing istotnedla małych i średnich przedsiębiorstw, 2011)
Development of new information technologies (IT) should meet user’s needs and additionally be innovative enough to attract particular users. In the case of small and medium sized enterprises (SMEs), information technologies should support very different facilities ofthis group of users but in a very effective way. Undoubtedly, enterprises representing SMEshave specific features and expectations that are essential in acceptation of new solutions in IT.The aim of the paper is to discuss these properties and needs which are the basis for showing utility of cloud computing (CC) as a technology addressed to SMEs. In the most importantpart of the paper crucial offerings and features of CC are discussed and confronted with SME sexpectation
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 205, s. 123-130
Keywords: cloud computing; small and medium sized enterprise; IT features; SMEs requirements